A View on the Customs and the Constitutional Conventions as Subsidiary Sources of the Constitutional Law - Sinani, Blerton; Dumi, Alba (Mediterranean Journal of Social Sciences, 2012)
The aim of this research article is â€œdeveloping the topicâ€ which is being analyzed. The treated issues in this researcharticle, with constitutional â€“ juridical thematic, lay and focus in analyzing the customs and the constitutional conventions assubsidiary sources of the constitutional law, as a branch of the law, it presents illustrative and concrete examples from thepractice of the comparative constitutional law. This article shows special interests, mainly and firstly, in the development oftheoretic and juridical â€“ constitutional thought, and also treats professional and applicative issues. The juridical norms, if we usea figure of speech, are â€œthe spinal cordâ€ or â€œthe essenceâ€ of the constitutional law as a branch of the law. As a matter of fact, thejuridical norms constitute the content of the constitutional law. The juridical norms that regulate the social relations, whichcompose the object of the constitutional law are called constitutional â€“ juridical norms, and this is how they diverge from thejuridical norms that regulate other social relations, which on the other side, are included in other branches of the law (in theadministrative law, in the criminal law, in the civil law etc)1. The constitutional â€“ juridical norms are juridical sui generis norms(norms of a special kind), that are â€œregulated or sanctioned by the stateâ€ for the juridical regulation of the social relations whichare created during the activity of the highest and most important organs of a given state.